Mobiliser des partenaires pour lutter contre le VIH/sida : les risques de la démobilisation institutionnelle en cas d’épidémie faible et concentrée. Le cas du programme Amali au Maroc - David Goeury (L’Année du Maghreb)
In Morocco, the program of income generating activities for people infected or affected by HIV(Amali) reveals the difficulty of jointly mobilizing health NGOs specializing in HIV and AIDS with development organizations in a context of a weak and concentrated epidemic. Despite the positive effects among beneficiaries, operators specialized in development (NGO and social development agency) are struggling to become involved on a long-term basis with particularly vulnerable and, above all, highly stigmatized people (male and female survival sex workers; men who have sex with men). In addition, the nomination of leaders from the Islamist movement at the ministry of social affairs has led to a divergence of intervention model between the social allocation based on criteria of precariousness and economic integration through the development of an autonomous activity, which allows the beneficiary to rebuild a social network. We will rely on observations carried out in 2015 within the framework of the ANRS 12305 project “IGA and key populations infected or affected by HIV in Morocco”: a survey of 500 potential beneficiaries of the Amali program conducted in five cities (Agadir, Casablanca, Rabat, Tangier, Taroudant) implemented with ALCS ; a survey of 25 Amali project leaders in these same cities and 22 semi-directive interviews with all the stakeholders of the partner organizations (ALCS, ADS, local associations) in the seven cities where the project is implemented (Agadir, Casablanca, Fez, Marrakech, Rabat, Tangier, Taroudant). The Amali program ended due to the financial disengagement of ADS in favor of a future universal social allowance that has yet to be implemented. This decision appears to be a means of not taking into account the specificities of PLHA (female sex workers, men who have sex with men). It will result in maintaining their status as highly stigmatized marginalized people. This stigmatization currently prevents the extinction of the HIV-AIDS epidemic in Morocco.